Paraoxonase and arylesterase levels in rheumatoid arthritis - Isik, A.; Koca, S. S.; Ustundag, B.; Celik, H.; Yildirim, A. (Springer, 2007)
It was reported that lipid peroxidation (LPO) products increase in rheumatoid arthritis (RA) patients and increased LPO products reduce many antioxidants. Lipid hydroperoxides (LOOHs) are byproduct of LPO. Paraoxonase (PON), arylesterase (ARE), free sulfhydryl (SH) groups, and ceruloplasmin (CP) are enzymes or proteins with antioxidant characteristics. This study aims to determine the levels of LOOHs and SH, and the activities of PON1, ARE, and CP in RA patients. The study included 47 active RA cases and 23 healthy volunteers. The levels of LOOHs and SH, and the activities of PON1, ARE, and CP were determined using appropriate methods. Student's t test and Spearman's correlation analysis methods were employed in the statistical evaluation. The level of LOOHs was found to be higher (p < 0.001), while the level of SH and the activities of PON1, ARE, and CP were found to be lower (p < 0.001, < 0.001, < 0.01, and < 0.01, respectively) in the RA patient group when compared with the control group. There was a negative correlation between the level of LOOHs and the activity of PON1 in the patient group (r=-0.420 and p < 0.01). The results of our study indicate increased oxidant and decreased antioxidant presence in RA patients. PON1 and ARE are known to have antiatherosclerotic effects in addition to their antioxidant characteristics. As the decrease in these antioxidants, resulting from increased oxidative stress in RA patients, development of atherosclerosis besides tissue injury seems inevitable.
Keywords: arylesterase; lipid hydroperoxide; paraoxonase; rheumatoid arthritis